Methodological regulation and analytical- information support of potential management in the context of organizational development an enterprise - Kulikov, O. (Ways to Improve Construction Efficiency, 2023)
Ensuring the effectiveness of organizational changes is associated with the need to take into account risks and design actions to prevent the occurrence of conflict situations and overcome resistance to changes, the reasons for which may be the unnecessarily negative reflexive nature of the company’s staff’s perception of radical transformations. To assess the radicality of structural changes, it is proposed to use a methodical approach to positioning relevant projects in the space formed by integral assessments of the impact of the results of the implementation of such transformations on the organizational level of management, the level of the organization of the production process, and the level of the organization of personnel management. For the proposed scale for assessing the radicality of structural transformation projects, recommendations have been developed for the purposeful use of tools for countering resistance to organizational changes on the example of enterprises implementing construction projects. The main research hypothesis consists in the assumption that increasing the level of project management effectiveness depends on the effectiveness of cognitive mechanisms and is associated with the use of modern concepts of information modeling and integrated project implementation. The necessity of using a selective approach to the organization of planning structural changes has been proven, which is proposed to be carried out by selecting the following types of construction of the appropriate planning system: operational, focused mainly on optimizing relations and connections of units; design, which involves making changes in the principles of structural construction of the enterprise (in the range of choosing between the options of centralization or decentralization); autonomous, based on the support of strategic orientation and adaptive orientation of structural changes as an element of a constantly operating system of adaptation of the enterprise to changes in economic conditions.